82‐3: Late‐News Paper: Intense Pulsed Light‐Induced Highly Flexible Transparent Electrodes and Their Applications. Issue 1 (29th May 2019) - Woo, Kyoohee; Zhong, Zhaoyang; Kwon, Sin; Kim, Hyuntae; Jang, Yunseok; Kim, Hyunchang; Jo, Jeongdai
Abstract : Recently, various electronic devices, such as displays, sensors, and batteries have been widely demanded to be highly deformable. Accordingly, numerous efforts have been made to convert their essential components from rigid and bulky form onto flexible and thin one. For example, metal nanowire (NW) based flexible transparent electrode had been developed instead of conventional brittle indium tin oxide (ITO) transparent electrode. Here, we tried to create extremely flexible conductive features that can tolerate severe mechanical stress using intense pulsed light sintering process. Additionally, using a significant differences in adhesion between light‐exposed and non‐exposed regions with respect to the underlying substrate, it was confirmed that patterning of conductive electrodes could be easily accomplished on large area. The potential use of IPL treated electronic conductive features were clearly demonstrated by fabricating flexible OLED and touch sensor. Our results facilitate their widespread application in future electronics, such as flexible display and wearable sensors.